If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9x = -14 Combine like terms: 4x + 9x = 13x 13x = -14 Solving 13x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '13'. x = -1.076923077 Simplifying x = -1.076923077
| -60x+747=20 | | -20=-6x-4x | | 2m+4-6m=8(m-1) | | X-3/6=2/8 | | -19.3x=248.97 | | 10z-z=2+2z-1-18 | | y=3.4x+5.1 | | 1=-2-x/5 | | -3a+2b-2c+8a-b=0 | | -11=m+6 | | 576=-16u | | (X+3y)(3y-x)= | | 4-2(3x+5)=36 | | -6x+747=0 | | 66=6a | | -5/4x=7 | | -60x+747=12 | | -5=4+s | | -104.78=-6.2(3n-1.1) | | 3x(6-2)-1= | | -7-8(4c+5)= | | 2(y+6)= | | X-2/13=5/13 | | 24=k | | 8p^2-16p-5=0 | | -3/4x=7/18 | | 25+3x=64 | | (6x+4)=180 | | 6-9x-4=-12+3x-10 | | p/4-6=3 | | 4x+15=6x+19 | | -16=1/7x |